THE GENUS INDIGOFERA L.(FABACEAE-PAPILIONNOIDAEAE) IN BURMA - M. Sanjappa (BRIN Publishing (Penerbit BRIN), 1984)
26 species of indigofera are found inburma. It includes 2 new pecies( I.maymayoensis and menghalayensis) and a new record (I.scabrida) A.key is provided to the species recongnised;descriptions,distribution and phenology are given.The specimens examined are cited